Джерела тіньових відносин, що виникають у сфері туристичного бізнесу: історико-порівняльний аспект - Нестерова, І.А. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Рассматриваются проблемы теневой экономики в сфере туристического бизнеса Украины, анализируются причини появления этого феномена. Делается вывод о едином характере проявления теневых отношений во всех сферах экономики. The article is devoted to the tourist business sphere in Ukraine as one of most world industries and such phenomena as «shadowing» in it. The author tries to analyze the reasons and conditions of this phenomena existing, gives some propositions to the strategy of tourist sphere de-shadowing.